2018
DOI: 10.1111/ene.13620
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular diseases may play a negative role in the prognosis of amyotrophic lateral sclerosis

Abstract: Our large, multicentre study demonstrated that, together with the known clinical factors that are known to be prognostic for ALS survival, hypertension and heart diseases (i.e. atrial fibrillation and heart failure) as well as haematological diseases are independently associated with a shorter survival. Our findings suggest some mechanisms that are possibly involved in disease progression, giving new interesting clues that may be of value for clinical practice and ALS comorbidity management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…Concomitant psychiatric diseases in ALS patients, whether prior or after this fatal diagnosis, may add strain on caregivers and pose important ethical challenges for support and end-of-life decisions along the course of this disease. Until now, only few register-based studies have taken into account the prognostic significance of simultaneous psychiatric illness in ALS, showing a mild negative influence of anxiety symptoms and other psychiatric disturbances in univariate analysis, whose effect was later unconfirmed in multivariate analysis (Körner et al, 2013; Mandrioli et al, 2018). Other studies examining the impact of neuropsychiatric symptoms in ALS, expressed mainly as behavioral alterations, failed to demonstrate any impact on survival (Mioshi et al, 2014; Burke et al, 2017).…”
Section: Prognostic Role Of Psychiatric Disturbances In Alsmentioning
confidence: 99%
“…Concomitant psychiatric diseases in ALS patients, whether prior or after this fatal diagnosis, may add strain on caregivers and pose important ethical challenges for support and end-of-life decisions along the course of this disease. Until now, only few register-based studies have taken into account the prognostic significance of simultaneous psychiatric illness in ALS, showing a mild negative influence of anxiety symptoms and other psychiatric disturbances in univariate analysis, whose effect was later unconfirmed in multivariate analysis (Körner et al, 2013; Mandrioli et al, 2018). Other studies examining the impact of neuropsychiatric symptoms in ALS, expressed mainly as behavioral alterations, failed to demonstrate any impact on survival (Mioshi et al, 2014; Burke et al, 2017).…”
Section: Prognostic Role Of Psychiatric Disturbances In Alsmentioning
confidence: 99%
“…The link between hypertension and ALS is currently less clear. Multiple associations have been made between hypertension and ALS onset and survival [116,129], but contradicting results have also been obtained by other studies [76,94,128]. This could possibly be explained by variations in methodology, and further studies are therefore required to confirm this association.…”
Section: Abnormal Vascular Changes In Alsmentioning
confidence: 87%
“…1 Most patients die of respiratory complications 3-5 years after its onset. 4,5 Takotsubo syndrome (TTS), also known as stress-induced cardiomyopathy, represents an acute heart failure syndrome characterized by ST-segment elevation and reversible left ventricular regional wall motion abnormalities (typically involving the apex). 1,2 Difficult swallowing is another frequent complication often requiring percutaneous endoscopic gastrostomy (PEG) in order to provide proper nutritional support and minimize the risk of aspiration pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Recent publications have reported that heart diseases, including atrial fibrillation and heart failure, are common in ALS patients and are independently associated with reduced survival. 4,5 Takotsubo syndrome (TTS), also known as stress-induced cardiomyopathy, represents an acute heart failure syndrome characterized by ST-segment elevation and reversible left ventricular regional wall motion abnormalities (typically involving the apex). 6,7 The precise pathogenesis of TTS remains unknown; a neurogenic origin with excessive catecholamine production causing microvascular spasm and direct cardiotoxicity may be involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation